Marital Satisfaction Among Dual-Earner Marriage Couples: Commuter versus Single Residences Couples - Chrishiannie, Chrishianie; Ginanjar, Adriana Soekandar; Primasari, Indira (UI Scholars Hub, 2018)
This study aimed to compare marital satisfaction in two types of dual-earner couples, namely commuter and single residence marriage couples. Commuter marriage couples are those who live in two separate residences due to their work demands for at least part of the week, whereas single residence couples live in the same residences. A sample of 239 couples filled out the Couple Satisfaction Index (CSI). Factorial ANOVA used to compare marital satisfaction of the two groups. The result showed that commuter marriage couples have higher marital satisfaction compared to single residence dual earner couple. Men in this study reported higher marital satisfaction compared to women.